Diagnosis of metastatic carcinoid in mesenteric lymph node by fine needle aspiration cytology - Naniwadekar Manjiri; Desai S; Dombale V; Kulkarni S (Wolters Kluwer Medknow Publications, 2008)
Although carcinoid tumor is a relatively common neoplasm in surgical pathology, fine needle aspiration cytology (FNAC) as a method of primary diagnosis has only been reported a few times. We report the case of a 55-year-old male patient who presented with colicky pain in the abdomen and a vague mass in the right lumbar region. Ultrasonographic study showed an enlarged mesenteric lymph node. Ultrasonography-guided FNAC revealed cellular smears with neuroendocrine cellular arrangement and morphology. The cytomorphologic characteristics of carcinoid tumors are distinctive enough for diagnosis. A diagnosis of metastatic carcinoid was given. 5-hydroxyindolacetic acid in 24-hour urine turned out to be high. Histopathology and immunohistochemistry studies also confirmed the diagnosis. Thus, FNAC can be a useful and safe tool in the diagnosis of carcinoid tumors.